Contextual Challenges to Safe Surgery in a Resource-limited Setting: A Multicenter, Multiprofessional Qualitative Study. Issue 3 (March 2018) - Scott, John W.; Lin, Yihan; Ntakiyiruta, Georges; Mutabazi, Zeta A.; Davis, William Austin; Morris, Megan A.; Smink, Douglas S.; Riviello, Robert; Yule, Steven
Abstract : Objectives: Safe surgery should be available to all patients, no matter the setting. The purpose of this study was to explore the contextual-specific challenges to safe surgical care encountered by surgeons and surgical teams in many in low- and middle-income countries (LMICs), and to understand the ways in which surgical teams overcome them. Background: Optimal surgical performance is highly complex and requires providers to integrate and communicate information regarding the patient, task, team, and environment to coordinate team-based care that is timely, effective, and safe. Resource limitations common to many LMICs present unique challenges to surgeons operating in these environments, but have never been formally described. Methods: Using a grounded theory approach, we interviewed 34 experienced providers (surgeons, anesthetists, and nurses) at the 4 tertiary referral centers in Rwanda, to understand the challenges to safe surgical care and strategies to overcome them. Interview transcripts were coded line-by-line and iteratively analyzed for emerging themes until thematic saturation was reached. Results: Rwandan-described challenges related to 4 domains: physical resources, human resources, overall systems support, and communication/language. The majority of these challenges arose from significant variability in either the quantity or quality of these domains. Surgical providers exhibited examples of resilient strategies to anticipate, monitor, respond to, and learn from these challenges. Conclusions: Resource variability rather than lack of resources underlies many contextual challenges to safe surgical care in a LMIC setting. Understanding these challenges and resilient strategies to overcome them is critical for both LMIC surgical providers and surgeons from HICs working in similar settings. Abstract : Supplemental Digital Content is available in the text